New insights on the Hirnantian palynostratigraphy of the rio Ceira section, Buçaco, Portugal - Lopes, Gilda (2014)
The Lower Palaeozoic successions of Portugal are well represented in the Central Iberian Zone (Cll), one of the main tectonostratigraphic domains of the Iberian Massif. Located in the CIZ, the Bu<;aco Syncline presents one of its most complete Palaeozoic sequences. With a NW-SE orientation, the Lower Palaeozoic lithostratigraphic succession, includes several Ordovician units that ranges from the Lower Ordovician (Tremadocian stage) to the Upper Ordovician (Hirnantian stage) and are unconformably overlain by the Silurian Sazes Formation, at least of Wenlock and Ludlow epochs, in the Rio Ceira Section (Fig.1). This sequence is also well known by its rich palaeontological content in macrofauna (e.g. trilobites, briozoans, echinoderms, ostracods, brachiopods, graptolites) and microfauna (conodonts, chitinozoans, acritarchs) (Delgado, 1908; Henry and Thadeu, 1971; Mitchell, 1974; Henry et al., 1974, 1976; ElaouadDebbaj, 1978; Henry, 1980; Paris, 1979, 1981; Romano, 1982; Romano et aI., 1986; Young, 1985, 1987, 1988,1989).